2014
DOI: 10.1002/iub.1324
|View full text |Cite
|
Sign up to set email alerts
|

Cells producing their own nemesis: Understanding methylglyoxal metabolism

Abstract: Methylglyoxal, which is technically known as 2-oxopropanal or pyruvaldehyde, shows typical reactions of carbonyl compounds as it has both an aldehyde and a ketone functional group. It is an extremely cytotoxic physiological metabolite, which is generated by both enzymatic and nonenzymatic reactions. The deleterious nature of the compound is due to its ability to glycate and crosslink macromolecules like protein and DNA, respectively. However, despite having toxic effects on cellular processes, methylglyoxal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 102 publications
(203 reference statements)
0
74
0
Order By: Relevance
“…Our results suggest an important biological role in the detoxification of toxic ketoaldehydes typified by methylglyoxal, formed as a by-product of the glycolytic pathway, as well as from threonine degradation and from lipid peroxidation [48,49]. Our previous studies have identified two pathways for degradation of methylglyoxal in trypanosomatids, either by conversion to d -lactate catalysed by trypanothione-dependent glyoxalases GLO1 and GLO2, or by conversion to l -lactate via methylglyoxal reductase and lactaldehyde dehydrogenase [25].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest an important biological role in the detoxification of toxic ketoaldehydes typified by methylglyoxal, formed as a by-product of the glycolytic pathway, as well as from threonine degradation and from lipid peroxidation [48,49]. Our previous studies have identified two pathways for degradation of methylglyoxal in trypanosomatids, either by conversion to d -lactate catalysed by trypanothione-dependent glyoxalases GLO1 and GLO2, or by conversion to l -lactate via methylglyoxal reductase and lactaldehyde dehydrogenase [25].…”
Section: Discussionmentioning
confidence: 99%
“…4 It is formed through various metabolic routes via both enzymatic and non-enzymatic pathways, predominantly the glycolytic pathway. 5 MG is produced in only small amounts under normal conditions, but its expression is greatly increased in hyperglycemic disorders such as diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of 2-oxoaldehydes such as methylglyoxal causes damage to cells by reacting with DNA and proteins and generating advanced glycation end products, and the glyoxalase is critical to limit this damage under conditions of oxidative stress such as caused by ionizing radiation (25,273). Furthermore, methylglyoxal can activate Nox in certain cells to increase superoxide, leading to induction of specific matrix molecules including fibronectin (74,120).…”
Section: B Cd47-dependent Regulation Of Redox Metabolites In Irradiamentioning
confidence: 99%